Successful Anesthetic Management Using Dexmedetomidine Sequentially with Propofol in the Asleep-Awake-Asleep Technique for Elderly Patients Undergoing Awake Craniotomy - Shunsuke Tachibana; Soichi Tanaka; Michiaki Yamakage (Case Reports in Anesthesiology, 2020)
Anesthesiologists should supply proper sedation and high-quality awakening in awake craniotomy anesthesia. At our institution, we perform an asleep-awake-asleep technique for awake craniotomy anesthesia by using short-acting anesthetic drugs, such as propofol and remifentanil. However, elderly patients do not wake adequately in our normal protocol and hence are unable to complete the required neurological tasks. In this case series, we present the anesthetic management of three elderly patients with sequent use of propofol and dexmedetomidine as sedative agents for awake craniotomy. We hypothesized that this anesthetic protocol is advantageous in awake craniotomy management. For the awake phase, all patients were adequately awake and performed neurological tasks without adverse events and agitation. The use of dexmedetomidine sequentially with propofol in an asleep-awake-asleep technique for awake craniotomy in elderly patients might shorten the time to awakening and provide clear awakening.